(untitled) (Research, Society and Development, 2021)
Chronic Kidney Disease (CKD) is an injury that causes progressive impairment of exocrine and endocrine renal functions. A very common complication is anemia, caused by reduced erythropoietin production, iron deficiency and inflammation. Evidence demonstrates that vitamin D has effects on anemia of inflammation, through the increase in erythrocytes and decrease in pro-inflammatory cytokines. This study aims to review the effects of vitamin D supplementation on 25(OH)D2 concentrations, on anemia markers and on PTH levels. This is an integrative review carried out through the search and selection of original publications, in english and portuguese, indexed in PubMed, Web of Science and Science Direct databases belonging to the 2010-2020 range. The results pointed to 25(OH)D2 concentrations compatible with normality after vitamin D supplementation. In five studies, there was no change in hemoglobin and PTH levels, and in four studies there was a reduction in the dose of EPO or erythroid stimulating agent, attributing such effect on the role of calcitriol as a substrate for bone marrow erythropoietic cells. The study concluded that vitamin D supplementation had beneficial effects for correction of 25(OH)D2 deficiency, however, it reinforces the controversy about the behavior of vitamin D on the improvement of anemia markers and PTH levels in patients with DRC. Therefore, it is suggested that the beneficial effect of vitamin D on anemia in renal patients may be independent of PTH suppression.